Soil Permeability Studies in the Reclaimed Saline and Alkaline Soils - Misra, S.G.; Sharma, D.P. (Journal of Soil and Water Conservation, 2022)
Permeability is a specific property of soils which is a measure of readiness with which soils transmit water. In other words, it is the velocity of water flow which can be measured either in inches or centimeters per hour. Many investigators have found that upon leaching alkali soils, the rate of water penetration diminishes as the salts are leached out. It becomes especially pronounced when Nasalts comprise a high percentage of the total salts. Hissink (1907) obtained interesting results by using 0.17N solutions of different chlorides. The samples treated with NaC1 or KO were found impervious to water whereas water passed through the soils which were previously treated with calcium chloride. He found that basexchange was probably responsible for these variations in soil permeability.Gedroiz (1929) also made systematic investi-gations on the subject. He showed that permeability of the soil is greatly reduced by replacing exchangeablebases, especially Ca" ions with Ne ions. Soil permeability is greatly affected when soil is wetted to the desired depth within a limited period of water application.